Carbofuran Induced Oxidative Stress Mediated Alterations in Na+‐K+‐ATPase Activity in Rat Brain: Amelioration by Vitamin E. Issue 7 (27th May 2014) - Jaiswal, Sunil Kumar; Siddiqi, Nikhat Jamal; Sharma, Bechan
ABSTRACT Pesticides cause oxidative stress and adversely influence Na+‐K+‐ATPase activity in animals. Since impact of carbofuran has not been properly studied in the mammalian brain, the ability of carbofuran to induce oxidative stress and modulation in Na+‐K+‐ATPase activity and its amelioration by vitamin E was performed. The rats divided into six groups received two different doses of carbofuran (15% and 30% LD50) for 15 days. The results suggested that the carbofuran treatment caused a significant elevation in levels of malonaldehyde and reduced glutathione and sharp inhibition in the activities of super oxide dismutase, catalase, and glutathione‐S‐transferase; the effect being dose dependent. Carbofuran at different doses also caused sharp reduction in the activity of Na+‐K+‐ATPase. The pretreatment of vitamin E, however, showed a significant recovery in these indices. The pretreatment of rats with vitamin E offered protection from carbofuran‐induced oxidative stress.